Peran Kesetaraan Gender dalam Keluarga sebagai Pilar Keadilan Sosial - Agustina, Dewi; Masry, Rifqa; Rahmadani, Arini Dwi; Karolina, Josepin; Panggabean, Azuhra Widriyani; Zahra, Annisa; Rambe, Raudhiyah Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
Gender equality in the family is an important element in building a just and sustainable society. This research aims to explore the role of women in the family and the challenges faced in realizing gender equality, especially in the context of a strong patriarchal culture in Indonesia. Using a literature study method with a qualitative descriptive approach, this research examines ten relevant scientific articles in the time span of 2020 to 2025. The results show that women not only carry out domestic roles, but also play an active role in the family economy, children's education, and household decision-making. Awareness of the importance of equitable role sharing continues to increase, supported by education and education programs. However, social reality still shows male dominance in the family, as well as gender stereotypes that prevent women from being fully empowered. Local cultures such as the Dayak community show that local wisdom can be a force in creating equality. Therefore, collaborative efforts are needed between families, communities and the state through education, women's empowerment, and alignment of understanding of religious and cultural values, so that gender equality can truly be applied fairly and equally in family life in Indonesia.